Tailor-made material characteristics of bacterial cellulose for drug delivery applications in dentistry - Weyell, Peter; Beekmann, Uwe; Kuepper, Christine; Dederichs, Marco; Thamm, Jana; Fischer, Dagmar; Kralisch, Dana (Carbohydrate Polymers, 2019)
Bacterial cellulose (BC) has shown high potential as innovative wound dressing and drug delivery system. Bringing both together, drug-loaded BC was investigated for applications in dental therapies such as dental extraction or mucosal transplantation. Both applications would benefit from a material which degrades under physiological conditions, and from an antibiotic environment. Consequently, periodate-oxidation of BC was investigated to facilitate modified degradation behaviour. A periodate concentration of 0.14 mol/L at ϑ = 25 °C and t = 8 h resulted in a material loss of <10%, but at the same time a sufficient degree of degradation. Additionally, native and oxidised BC loaded with doxycycline was tested for prophylaxis against infection. An in vitro-toxicity test (MTT assay) provided a first confirmation of biocompatibility, whereas agar diffusion tests proved antibiotic efficiency against pathogenic oral bacteria. Release studies of the drug from native and oxidised BC confirmed a comparative biphasic release behaviour.
CRIS-Team Scopus Importer:2020-10-13
Keywords: Bacterial cellulose; Degradation; Dentistry; Doxycycline; Drug release